Genome-wide characterization and expression analysis of the GATA transcription factor family in response to salt and drought stress in barley (Hordeum vulgare L.) - Zhang, Haitao; Yu, Peng; Xiao, Hongwu; Wang, Chengyu; Yan, Xiaofeng; Zhang, Xiaoqin (Frontiers in Plant Science, 2025)
GATA transcription factors play a crucial role in regulating plant growth and development as well as stress responses. However, systematic analysis of GATA genes in barley remains uncharacterized, and their functional roles in salt and drought stress responses are poorly understood. This study conducted genome-wide identification and gene expression analysis of the GATA transcription factor family in barley through bioinformatics approaches. A total of 27 HvGATA genes were identified and divided into 4 subfamilies (I-IV), which were unevenly distributed on 7 chromosomes. Overall tertiary structural similarity of GATA proteins existed with differences, but similarity within the same subfamily was higher. Fragment repetition has been identified as the main driving factor for the expansion of the HvGATA family. Members of the same subfamily exhibit highly conserved exon-intron structures and motif compositions, indicating strong functional conservation among subfamilies. Cis-element analysis of the HvGATA promoter reveals potential regulatory complexity and enrichment of stress-responsive elements related to hormone signals (such as abscisic acid) and drought stress responses. qRT-PCR analysis showed that at 6 h after salt treatment, HvGATA1, HvGATA19, and HvGATA25, were significantly up-regulated (P < 0.05). Under drought treatment, at least three HvGATA genes (HvGATA1, HvGATA19, and HvGATA25) showed dynamic expression patterns, which were down-regulated and up-regulated at 2 h, 24 h, and 12 h, respectively, indicating that they have potential roles in regulating salt tolerance and drought tolerance of barley. This research provides new insights into the molecular mechanisms of salt and drought tolerance in barley and offers potential targets for enhancing the crop’s stress resistance under abiotic stresses.